Development of Play Model: Efforts to Improve Basic Movement Skills for Elementary School Students - Ahmad Karisman, Vicki; Asmawi, Mochamad; Samsudin,; Firmansyah Dlis,; Jufrianis, (Technium Social Sciences Journal, 2020)
Basic movement skill is important in performing movements in any sport activities. Having good essential movement skills will make it easy for someone to do sports. One effort that should be possible is through the development of a play model. The purpose of this study was to develop a play model and the the effectiveness of a play model on basic movement skills. Research and development with Analyze Design Develop Implementation and Evaluation (ADDIE) was employed to develop play models. The play model was designed in such a way through the stages of identification, game user targets, learning outcome, game time, overall goals, game variations and the final part of the game. This study was participated by third grade elementary students with 84 students in total with an average age of boys (± 9.5 years), and girls (± 9.7 years). The treatment was carried out 16 times for twice a week during class break. This study used three instruments, namely student perception questionnaire, knowledge test and the Test of Gross Motor Development (TGMD-2), with locomotor test items and object skills. This study had produced a play model product and shown a significant effect of developing a playing model on improving students' basic movement skills